The influence of nutrition level on occurence of lenee defects among children in kindergarten and early school age - Wojtanowski, Wiesław (Health Promotion & Physical Activity, 2016)
Introduction: The aim of the research was to assess the frequency of occurance of knee faults as well as the influence of nutrition level expressed in BMI, on setting of knees among children in kindergarten and early school age. Material nad methods: The research included boys aged 4-7 form Kindergarten No. 33 in Tarnow and Primary School No. 18 in Tarnow. The measurement concerned basic somatic features like body height and mass as well as shape of lower limbs. The received results served to carry out an assessment of nutrition level expressed in BMI and knee faults among the examined boys. Results: Nutrition level in the group of the examined does not differ from the standard. Among the examined, 26 cases of abnormalities were stated, including: 11 cases of intense valgus, 5 cases of varus and 27 cases of physiological valgus. In particular age groups 10 cases of overweight and 8 cases of obesity were stated. Conclusions: Relevant correlation occurs between the BMI value and the setting of knees.